2009
DOI: 10.1063/1.3268475
|View full text |Cite
|
Sign up to set email alerts
|

Electric field driven quantum phase transition between band insulator and topological insulator

Abstract: We demonstrate theoretically that electric field can drive a quantum phase transition between band insulator to topological insulator in CdTe/HgCdTe/CdTe quantum wells. The numerical results suggest that the electric field could be used as a switch to turn on or off the topological insulator phase, and temperature can affect significantly the phase diagram for different gate voltage and compositions. Our theoretical results provide us an efficient way to manipulate the quantum phase of HgTe quantum wells. PACS… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
34
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 56 publications
(36 citation statements)
references
References 16 publications
1
34
0
1
Order By: Relevance
“…In the case of 2D TIs (i.e., quantum spin Hall systems), still another factor affecting the band topology is an electrostatic scalar potential or an external electric field as an effective continuous model predicts that potential difference between upper and lower surfaces can transform topologically nontrivial thin films of Bi 2 Se 3 into topologically trivial ones (17,18). Actually, a model calculation shows that external electric fields can drive the quantum phase transition between TIs and NIs in HgTe quantum wells (19). It has been predicted that thin films of tetradymite semiconductors recently found to be 3D strong topological insulators can be 2D TIs or NIs depending on the thickness (20).…”
mentioning
confidence: 99%
“…In the case of 2D TIs (i.e., quantum spin Hall systems), still another factor affecting the band topology is an electrostatic scalar potential or an external electric field as an effective continuous model predicts that potential difference between upper and lower surfaces can transform topologically nontrivial thin films of Bi 2 Se 3 into topologically trivial ones (17,18). Actually, a model calculation shows that external electric fields can drive the quantum phase transition between TIs and NIs in HgTe quantum wells (19). It has been predicted that thin films of tetradymite semiconductors recently found to be 3D strong topological insulators can be 2D TIs or NIs depending on the thickness (20).…”
mentioning
confidence: 99%
“…14 It has been recently demonstrated that a transition between BI and TI phases can be driven either by electric field 15,16 , applied along the growth direction, or by temperature 17,18 . However, the mentioned works were focused on the evolution of the band structure due to transition between BI and TI phases only, while temperature and electric field effects in the SM phase were ignored.…”
mentioning
confidence: 99%
“…Последнее открывает допол-нительные возможности для создания перспективных " топологических" приборов, работающих с использова-нием краевых каналов проводимости [19]. К настоящему времени теоретически рассматривались возможности осуществления фазового перехода в КЯ HgTe/CdHgTe между состояниями тривиального и топологического изоляторов с помощью внешнего электрического по-ля [20,21], температуры [10,21,22] и давления [22]. Экс-периментально качественное изменение зонного спектра и наличие такого перехода при изменении темпера-туры впервые было продемонстрировано с помощью транспортных [10] и магнитооптических измерений [23].…”
Section: международный симпозиум "unclassified